The paleontological collection of Egidio Feruglio at MUST - Battista, Francesco (2018)
Many fossil specimens whose collection is attributable to Egidio Feruglio were found in the repositories of the Paleontology Museum in the Department of Earth Sciences of ‘Sapienza’ University of Rome, soon became MUST. The material can be traced back to the activity which Feruglio did in Argentina during his two stays between the twenties and forties of the twentieth century. Different available information about this material mainly deriving from tags, label and hand written notes combined with specimens, were organized and are here provided as subsidiary to future museum’s activities.